Facts Sheet: Gender makes the diference in conservation and sustainable development iniciatives / Eric, Hidalgo - Hidalgo, Eric (San José, Costa Rica : IUCN, 2004)
Gender makes the difference, why gender makes a difference in agriculture initiatives, why gender makes a diference in biodiversity initiatives; climate change and disaster mitigation, why gender makes a difference in climate change and disaster mitigation initiative, corporate social responsability, why gender makes the difference in energy initiatives, fair trade helps in the following ways, fisheries and aquaculture in coastal zones, why gender makes a diference in medicinal plants initiatives.
Illustrations
Col. Soc
Keywords: 1. CRECIMIENTO-DESARROLLO 2. GENDER DIFFERENCE-AGRICULTURE 3. BIODIVERSITY-INICIATIVE 4. SOCIOLOGY